2016
DOI: 10.1186/s13008-016-0020-7
|View full text |Cite
|
Sign up to set email alerts
|

The structure and regulation of Cullin 2 based E3 ubiquitin ligases and their biological functions

Abstract: BackgroundCullin-RING E3 ubiquitin ligase complexes play a central role in targeting cellular proteins for ubiquitination-dependent protein turnover through 26S proteasome. Cullin-2 is a member of the Cullin family, and it serves as a scaffold protein for Elongin B and C, Rbx1 and various substrate recognition receptors to form E3 ubiquitin ligases.Main body of the abstractFirst, the composition, structure and the regulation of Cullin-2 based E3 ubiquitin ligases were introduced. Then the targets, the biologic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
51
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(52 citation statements)
references
References 149 publications
1
51
0
Order By: Relevance
“…Therefore, Twist1 promoted Cul2 mRNA transcription but not translation. Cul2 has been predicted to be a tumor suppressor protein because of its association with the von Hippel-Lindau gene and ubiquitinated HIFa degradation (18,19). However, it has also been reported that Cul2 is required for normal vasculogenesis and involved in cell-cycle regulation (20) and that it promotes gastric cancer progression (35,36).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, Twist1 promoted Cul2 mRNA transcription but not translation. Cul2 has been predicted to be a tumor suppressor protein because of its association with the von Hippel-Lindau gene and ubiquitinated HIFa degradation (18,19). However, it has also been reported that Cul2 is required for normal vasculogenesis and involved in cell-cycle regulation (20) and that it promotes gastric cancer progression (35,36).…”
Section: Discussionmentioning
confidence: 99%
“…Cullin2 (Cul2) is a core component of multiple ECS (ElonginB/C-CUL2/5-SOCS-box protein) E3 ubiquitin-protein ligase complexes, which mediate the ubiquitination of target proteins. Cul2 was predicted to be a tumor-suppressor protein that degrades ubiquitinated HIFa (18,19). However, it has also been reported that Cul2 is required for normal vasculogenesis and is involved in cell-cycle regulation (20).…”
Section: Introductionmentioning
confidence: 99%
“…Twist as an important EMT-TF that directly or indirectly governs the transcription of EMT-associated genes, thereby decreasing epithelial markers, such as E-cad, and increasing mesenchymal cell markers, including vimentin [54]. Cullin2 (Cul2) is a core component of multiple ElonginB/C-CUL2/5-SOCS-box protein (ECS) E3 ubiquitin-protein ligase complexes that mediate the ubiquitination of target proteins [55,56]. A study has validated that Twist1 promotes Cul2 transcription by binding to the Cul2 promoter and increases the pre-mRNA levels of Cul2.…”
Section: Regulation Of Twist On Vimentin By Circrnasmentioning
confidence: 99%
“…First isolated as a partner of specific protein kinase C isoforms, for which it was named receptor for activated C-kinase (4–8), RACK1 has also been shown to interact with a considerable number of other signal transduction proteins, including the cAMP-specific phosphodiesterase PDE4D5 (917), the tyrosine kinase oncoproteins SRC (1821), FLT1 (22), and FAK (23), protein serine phosphatase PP2A (2426), the MAPKs JNK1 and ERK1/2 (27), VARP (28), phospholipase C (29), the NMDA receptor (3033), cytokine and growth factor receptors (3438), G sβγ (3942), selected 14.3.3 isoforms (43) and likely other signaling proteins (4447). RACK1 also interacts with members of complexes that play important roles in protein degradation, such as the Cullin-2 based E3 ubiquitin ligases (48;48;49), as well as certain enzymes of unclear cellular function, such as inositol-requiring enzyme 1 (IRE1; refs, (50)). RACK1 also may interact with elements of the cytoskeleton, including β-integrins (5156) and β-actin (21;21;57).…”
Section: Introductionmentioning
confidence: 99%